Design of 3D Modeling and Interaction on the SEAMOLEC Training Web - Farhan, Muhammad; Fris Okta Falma (TOFEDU: The Future of Education Journal, 2025)
This report is prepared as part of the Final Project titled "Design of 3D Modeling and Interaction on the SEAMOLEC Training Web." The main objective of this study is to fulfill one of the curriculum requirements for completing the Diploma Four (D-IV) Program at the Vocational School of Universitas Negeri Padang. During the completion of this final project, the author received considerable support from various parties, including intellectual guidance, moral encouragement, and material assistance. This project involved effective time management, where the author planned to complete the work within one week, starting from theme determination to the training publication. On the fifth day, the author conducted evaluations and revisions of the videos and prototypes created, and on the sixth and seventh days, focused on finalizing the training project. Visual appeal was one of the primary focuses of this training. An attractive design and layout are crucial to engage participants, making them feel comfortable and interested in joining the training. Furthermore, the 3D models used in the training must meet specific criteria to ensure the learning outcomes can be effectively tested, ranging from shape selection to color choices. Therefore, this report aims not only to meet academic requirements but also to contribute to the development of more interactive and engaging training methods through the use of 3D modeling technology. The author hopes that the results of this project will be beneficial for the advancement of education and training in the future.